2009
DOI: 10.1103/physrevc.79.051902
|View full text |Cite
|
Sign up to set email alerts
|

Long range correlations and the soft ridge in relativistic nuclear collisions

Abstract: Relativistic Heavy Ion Collider experiments exhibit correlations peaked in relative azimuthal angle and extended in rapidity. Called the ridge, this peak occurs both with and without a jet trigger. We argue that the untriggered ridge arises when particles formed by flux tubes in an early Glasma stage later manifest transverse flow. Combining a blast wave model of flow fixed by single-particle spectra with a simple description of the Glasma, we find excellent agreement with current data. Correlation measurement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
249
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(263 citation statements)
references
References 37 publications
13
249
0
1
Order By: Relevance
“…The various harmonic flows were attributed to fluctuations in the initial-state A-A geometry coupled to radial expansion of the bulk medium [12,13]. In an alternative scheme the elongated SS 2D peak was explained in terms of glasma flux tubes coupled to radial flow [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The various harmonic flows were attributed to fluctuations in the initial-state A-A geometry coupled to radial expansion of the bulk medium [12,13]. In an alternative scheme the elongated SS 2D peak was explained in terms of glasma flux tubes coupled to radial flow [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that the "hydrodynamical" type models with fluctuations in the initial volume and/or saturation effects may be relevant for the correlations discussed here [11][12][13]. Such models may also relate these correlations to the famous "ridge" effect [14,15]. However, collective effects are absent in PYTHIA and in our naïve model.…”
Section: Introductionmentioning
confidence: 65%
“…This will not change if we average the numerator and denominator in (14) separately. We see that this simplified model disagrees strongly with the pp data: the values of are always negative, whereas in the data they are positive.…”
Section: Discussionmentioning
confidence: 99%
“…Similar ∆φ-∆η correlations associated with a near-side jet have also been observed by the PHENIX Collaboration [16,17] and the PHOBOS Collaboration [18]. While many theoretical models [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] have been proposed to discuss the jet structure and related phenomena, the ridge phenomenon has not yet been fully understood.…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, both J z and α 3 commute with the operator acting on ψ(r, φ, z, t) in Eq. (35). Upon using the representation in Ref.…”
Section: Early Particle Production At High Energiesmentioning
confidence: 99%